Catalytic removal of NO and chlorobenzene over Ce-Mn-W-Zr-Ox/TiO2: Performance study of hollow spheres effect. (1st December 2021) - Jin, Qijie; Xue, Zhiwei; Zhi, Xiaohuan; Ji, Wenyu; Shen, Yuesong; Zeng, Yanwei
Graphical abstract: Highlights: CMWZ/H-TiO2 catalyst was suitable for co-catalytic removal of NO and chlorobenzene. The hollow structure of TiO2 accelerated the activation of reaction molecules. NH4 + and –NH2 were the main ammonia species in the SCR reaction. The structure of Chlorobenzene is completely destroyed at above 350 °C. Abstract: Co-catalytic removal of multiple pollutants was able to reduce operating costs of enterprises, which was the main development direction for the waste incineration industry. In this work, the influence of hollow structure on the catalytic performance was investigated. The coexistence of anatase and rutile phases in the hollow structure accelerated the activation of reaction molecules on the catalyst surface and promoted the improvement of reaction activity. Furthermore, the confinement effect of the hollow structure may promote the adsorption of reaction molecules inside the sphere, and prolong the reaction time of the molecules at the active site of the catalyst, thereby promoting the progress of the reaction. It was the excellent redox performance and fast oxygen migration ability of hollow structure that made CMWZ/H-TiO2 had excellent performance in co-catalytic removal of NO and chlorobenzene. Finally, NH4 + and –NH2 were the main ammonia species in the SCR reaction, and –NO2 was the main NO adsorption species, so the reaction of SCR on the CMWZ/H-TiO2 catalyst followed the L-H mechanism. For the degradation of chlorobenzene, the main intermediate products at low temperature were phenolic species and maleate species. At high temperature, the intermediate products of chlorobenzene were mainly maleate species, bidentate carbonate species and carbonate species.